2024
DOI: 10.1039/d3ee03921h
|View full text |Cite
|
Sign up to set email alerts
|

Constructing highly durable reversal-tolerant anodes via integrating high-surface-area Ti4O7 supported Pt and Ir@IrOx for proton exchange membrane fuel cells

Zheng Li,
Yongbiao Mu,
Qing Zhang
et al.

Abstract: Fuel starvation during fuel cell operation inevitably leads to high potential anodes, which causes carbon corrosion and catalyst layer collapse and poses a challenge to the durability of proton exchange...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…Li et al recently synthesized fine Ti 4 O 7 particles using our carbothermal reduction reaction route with some modifications. 37 The σ -value reported in our paper 36 was well reproduced by Li et al 37 as shown by the open 36 and filled circles, 37 respectively, in Fig. 4(k).…”
Section: Carbon-support-free Platinum/platinum Alloy Catalystssupporting
confidence: 85%
See 3 more Smart Citations
“…Li et al recently synthesized fine Ti 4 O 7 particles using our carbothermal reduction reaction route with some modifications. 37 The σ -value reported in our paper 36 was well reproduced by Li et al 37 as shown by the open 36 and filled circles, 37 respectively, in Fig. 4(k).…”
Section: Carbon-support-free Platinum/platinum Alloy Catalystssupporting
confidence: 85%
“…The selected P differs across these papers, and the specific P value is not even described in some papers, making it difficult to compare the reported σ -values of non-carbon supports against each other. Some researchers reported σ at various P values, and the σ values of Ti 4 O 7 , 36–38 mixed Magnèli-phase Ti n O 2 n −1 (4 ≤ n ≤ 6), 39 commercial TiO 2 (ref. 38) and commercial carbon black 38 are compared in Fig.…”
Section: Carbon-support-free Platinum/platinum Alloy Catalystsmentioning
confidence: 99%
See 2 more Smart Citations
“…RTAs, through their unique material design and structure, can maintain stable performance even during voltage reversal, thus eliminating the need for active cell voltage monitoring. The advancement in RTAs technology primarily involves the strategic integration of various OER catalysts, including IrO 2 , RuO 2 , TiO 2 , and IrRu. Particularly, the integration of Ir-based catalysts has been noted for its efficiency in promoting proton and electron production at the anode through OER instead of carbon oxidation . The deployment of monodisperse IrO X on Pt/C (Pt-IrO X /C) has been instrumental in transforming RTA materials for PEMFCs by ensuring a relative distribution of IrO X nanoparticles on the carbon support, boosting the efficiency of both Pt and IrO X . , However, employing additional Ir-based catalytic additives encounters substantial economic challenges due to their scarcity and elevated cost. In light of the significant expenses associated with these catalysts, it is essential to devise RTAs that can operate effectively with lower amounts of OER catalysts, thereby enhancing the overall cost efficiency of these systems. In a more progressive design, research efforts have focused on replacing Pt with multifunctional alloy catalysts that are adept at both hydrogen and oxygen reaction activities. This advancement represents a critical balance between catalytic activity and stability, especially for OER applications, marking a notable stride in RTA catalyst layer design. However, the complexities of synthesizing these alloys and ensuring their multifunctional catalytic activity present significant technical hurdles.…”
Section: Introductionmentioning
confidence: 99%